PERILAKU TIDAK MEMILIH DALAM PEMILIHAN PRESIDEN DAN WAKIL PRESIDEN REPUBLIK INDONESIA TAHUN 2014 (Studi Kasus Kecamatan Pekanbaru Kota) - Wulandari, Sri; Tinov, M. Y. Tiyas (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Behavior does not choose a conscious decision by someone to not use its voting rights by not attending the polling stations on the implementation of the general election. This study examines the behavior is not picking on people in the District of Pekanbaru City election of the President and Vice President in 2014. The authors are keen to do this research, because in democratic countries, elections or election of President and Vice President is an instrument of the implementation of democracy, but Pekanbaru City Subdistrict Subdistrict society many do not exercise their voting rights in the implementation of the democratic party. The research problems are "why some people do not participate in the election of President and Vice President in 2014?" This study aims to determine the reasons that dominate the public District of Pekanbaru City who do not exercise their voting rights by using three categories of reasons behavior did not choose that reason technical, political reasons and ideological reasons. This type of research is descriptive quantitative method with a sample of 100 people Pekanbaru Kota sub-district, and data collection techniques that do are questionnaires, interviews and documentation enclosed.The results of this study, that the reason for not selecting the most dominating are technical reasons such as work, pain, and out of town, which is about 57%. Of these three indicators, the reasons prefer to work rather than come to the polls to choose the highest reason in the category of technical reasons, This is because the majority of respondents work as traders that are more concerned with economic interests rather than participate in political activities. Another is political and ideological reasons.Keywords: Non voting behavior, President and Vice President